Breaking into the lab : engineering progress for women in science - Rosser, Sue Vilhauer (New York University Press, 2011)
Why are there so few women in science? In Breaking into the Lab, Sue Rosser uses the experiences of successful women scientists and engineers to answer the question of why elite institutions have so few women scientists and engineers tenured on their faculties. Women are highly qualified, motivated students, and yet they have drastically higher rates of attrition, and they are shying away from the fields with the greatest demand for workers and the biggest economic payoffs, such as engineering, computer sciences, and the physical sciences. Rosser shows that these continuing trends are not only.